Small-Group Activity to Apply Zero-Order Pharmacokinetic Principles - Kelly Karpa; Sesilya Whaley; Philip Moore (Association of American Medical Colleges, 2015)
Abstract Introduction Due to the transition from traditional to integrated curricula, and the merging of pharmacology departments with other disciplines, basic pharmacological principles are no longer a focus. At our institution, basic pharmacokinetic concepts and terminology are introduced to medical students during their first month as medical students. It is important that students have the underlying context and vocabulary to explain how drugs are handled by the body before they are exposed to specific pharmacologic agents with unique pharmacokinetic properties. The purpose of this module is to provide health professions students with an opportunity to practice applying clinically relevant, basic zero order pharmacokinetic concepts. Methods In this small group activity, students are tasked with applying knowledge of zero order pharmacokinetic principles using a drug exemplar (ethanol) with which most of them have some familiarity (e.g., personal use or use among family, friends, or patients). This case was first introduced in the classroom with an interprofessional group of learners (nine third-year medical students, seven final-year pharmacy students, and three nurse practitioner students in the second year of their program). The second time, the case was used with a group of seven third-year medical students only. Results The session was highly rated both times by all students. Completed evaluations for the session were submitted by 25 of 33 participants. Twenty-four of the 25 respondents (96%) indicated that the session was worth their time. Students' mean rating of the zero order pharmacokinetic activity on a scale of 1 (poor) to 5 (excellent) was 4.1. No differences were observed between learners from different disciplines in their rating of the activity. Similarly, on the same scale, when students were asked to rate the extent to which the activity met learning objectives, the mean rating was 4.36. Discussion Given recent changes in our medical school curriculum that promote vertical integration of basic science concepts during the clinical years of medical school training and interprofessional education with students across disciplines, we plan to use this learning activity at our main medical school campus in a new "Integrated Basic Science" curriculum that has been developed specifically for 3rd year medical students.